2010
DOI: 10.1016/j.foodchem.2010.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and antioxidant capacities of 18 non-traditional tropical fruits from Brazil

Abstract: The bioactive compounds and antioxidant capacities of polyphenolic extracts of 18 fresh and dry native non-traditional fruits from Brazil were determined using ABTS, DDPH, FRAP and b-carotene bleaching methods. The study provides an adaptation of these methods, along with an evaluation of the compounds related to antioxidant potential. The results show promising perspectives for the exploitation of non-traditional tropical fruit species with considerable levels of nutrients and antioxidant capacity. Although e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

98
750
55
193

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,151 publications
(1,096 citation statements)
references
References 28 publications
98
750
55
193
Order By: Relevance
“…Rufino et al (2010) sugeriram uma classificação dos teores de fenóis totais como baixo (<100 mg EAG 100 g -1 ), médio (100-500 mg EAG 100 g -1 ) e alto (>500 mg EAG 100 g -1 ) na matéria fresca; dessa forma, a guavira pode ser considerada como fruto de médio teor de fenóis totais.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Rufino et al (2010) sugeriram uma classificação dos teores de fenóis totais como baixo (<100 mg EAG 100 g -1 ), médio (100-500 mg EAG 100 g -1 ) e alto (>500 mg EAG 100 g -1 ) na matéria fresca; dessa forma, a guavira pode ser considerada como fruto de médio teor de fenóis totais.…”
Section: Resultsunclassified
“…Perspectivas promissoras para exploração de frutos tropicais não tradicionais se devem aos níveis consideráveis de vitamina C, antocianinas, carotenoides e compostos fenólicos, além da capacidade antioxidante destes frutos (RUFINO et al, 2010). Muita atenção tem sido focada para a atividade antioxidante total presente em frutas e hortaliças, devido aos diversos constituintes presentes que possuem propriedades de reduzir o nível do estresse oxidativo (HASSIMOTO et al, 2005), e consequentemente diminuir o risco de diversas doenças cardivasculares, neurodegenerativas e câncer (HALLIWELL, 2007;KAUR;KAPOOR, 2002).…”
Section: Introductionunclassified
“…The focus of antioxidant studies in the Myrtaceae family from Brazil has been on edible fruits (Marin et al, 2008;Rufino et al, 2009Rufino et al, , 2010Pereira et al, 2012) with few reports on leaves (Coutinho et al, 2008;Salvador et al, 2011). Thus, our results contribute valuable knowledge about the bioactive properties of native Myrtaceae species.…”
Section: Discussionmentioning
confidence: 99%
“…The results found in the present study are similar to those reported by Cheel et al (2007) in strawberries and by Jiao and Wang (2000) in blackberries. Rufino et al (2010) analyzed the correlation between the phenolic compounds and the total antioxidant activity of 18 tropical fruits by the ABTS method, and they found positive and significant correlations (0.92). Thaipong et al (2006) evaluated the antioxidant activity of methanolic extracts of guava by the ABTS and DPPH assays and obtained a significant correlation between the two methods.…”
Section: Total Polyphenol Content and Antioxidant Activity Of Murtillmentioning
confidence: 99%